Evaluación ambiental y social al centro de faenamiento tena, mediante la aplicación de la matríz de leopold para proponer un plan de manejo ambiental - Ocaña Lescano, Jeimy Madeline (2016)
The research was done at Centro de Faenamiento Tena, which is located in San Jacinto, in Napo Province. This Center is characterized by giving a good service to the population. At the same time, it has some weaknesses related to the environmental aspect. Having knowledge about this problem, we have done an environmental and social evaluation about its resources. The methodology that we have applied to collect information were: surveys, check lists and the Leopold template. Once we had the information, we elaborated an Environmental Management Plan to minimize, mitigate and prevent inadequate actions. The results obtained through field work, the environmental and social evaluation in the template, showed us that the resource Water was the most polluted element, represented by (-8), considered as a VERY HIGH index in pollution according to the table of ranks. Through the chemical analysis of water taken as reference, the fecal coliform parameter exceeded the allowable limits established in the TULSMA, due to the fact that 1'200.000 CFU / 100mL was obtained and its limit is 10000 CFU / 100mL. This problem was evidenced from the saturation of the treatment plant. In social terms, the presence of CEFATE has increased the economic activity of the population and its development, in the matrix was obtained a value of (+8) considered as a VERY HIGH index in terms of positive impacts. Through this analysis, the WFP proposed the following programs: Training and Environmental Education, Prevention and Mitigation of Impacts, Waste Management, and the Monitoring and Monitoring program, with the intention of conserving the biodiversity of CEFATE. Key